2020
DOI: 10.1101/2020.04.16.045732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehension of computer code relies primarily on domain-general executive brain regions

Abstract: Computer programming is a novel cognitive tool that has transformed modern society. An integral part of programming is code comprehension: the ability to process individual program tokens, combine them into statements, which, in turn, combine to form a program. What cognitive and neural mechanisms support this ability to process computer code? Here, we used fMRI to investigate the role of two candidate brain systems in code comprehension: the multiple demand (MD) system, typically recruited for math, logic, pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

7
3

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 148 publications
(145 reference statements)
1
48
3
Order By: Relevance
“…We conducted an exploratory analysis to check whether engagement of the MD and/or language system in code comprehension varies with the level of programming expertise. We correlated responses within each system with independently obtained proficiency scores for Experiment 1 participants (see the paper’s website for details: https://github.com/ALFA-group/neural-program-comprehension ; Ivanova and Srikant, 2020 ; copy archived at swh:1:rev:616e893d05038da620bdf9f2964bd3befba75dc5) and with in-scanner accuracy scores for Experiment 2 participants. No correlations were significant (see Figure 4—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted an exploratory analysis to check whether engagement of the MD and/or language system in code comprehension varies with the level of programming expertise. We correlated responses within each system with independently obtained proficiency scores for Experiment 1 participants (see the paper’s website for details: https://github.com/ALFA-group/neural-program-comprehension ; Ivanova and Srikant, 2020 ; copy archived at swh:1:rev:616e893d05038da620bdf9f2964bd3befba75dc5) and with in-scanner accuracy scores for Experiment 2 participants. No correlations were significant (see Figure 4—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A network of left-lateralized frontal and temporal brain regions (here referred to as the language network) has been found to respond to written/spoken/signed words and sentences, but not to mental arithmetic, music perception, executive function tasks, action/gesture perception, or computer programming (Amalric & Dehaene, 2019;X. Chen et al, 2021;Fedorenko et al, 2011;Ivanova et al, 2020;Jouravlev et al, 2019;Liu et al, 2020;MacSweeney et al, 2002;Monti et al, 2009Monti et al, , 2012Pritchett et al, 2018). Similarly, investigations of patients with profound disruption of language capacity ( global aphasia) have shown that some of these individuals can solve arithmetic and logic problems, appreciate and create music, and think about others' thoughts in spite of their language impairment (Basso & Capitani, 1985;Luria et al, 1965;Varley et al, 2005;Varley & Siegal, 2000), providing converging evidence that language is subserved by domain-specific cognitive mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from neuroscience suggests that language processing is largely distinct from other aspects of cognition (Fedorenko & Blank, 2020;Fedorenko & Varley, 2016). A network of frontal and temporal brain regions (here referred to as the 'language network') has been found to respond to written/spoken/signed words and sentences, but not to mental arithmetic, music perception, executive function tasks, action/gesture perception, or computer programming (Amalric & Dehaene, 2019;Fedorenko et al, 2011;Ivanova et al, 2020;Jouravlev et al, 2019;Liu et al, 2020;Monti et al, 2009Monti et al, , 2012Pritchett et al, 2018). Similarly, investigations of patients with profound disruption of language capacity (global aphasia) have shown that these individuals can solve arithmetic and logic problems, appreciate music, and think about others' thoughts in spite of their language impairments (Basso & Capitani, 1985;Luria et al, 1965;Varley et al, 2005;Varley & Siegal, 2000), providing converging evidence that language and thought are neurally distinct.…”
Section: Introductionmentioning
confidence: 99%